New records of eutardigrades (Tardigrada) from Faial and Pico Islands, the Azores, with the description of two new species - Fontoura, Paulo; Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2008)
Five eutardigrade species from the Azores are reported in this study. Three of them are new records for the Azores, and another two, Macrobiotus almadai sp. nov. and Doryphoribius picoensis sp. nov., are new to science. Macrobiotus almadai sp. nov. belongs to the hufelandi group but it differs from the other species of the group in some characters of buccopharyngeal apparatus (narrow buccal tube, buccal armature without bands of teeth) and eggs (the terminal disc of processes may appear smooth, but in some orientations it shows very small teeth). Doryphoribius picoensis sp. nov. has cuticle with undulations and some small gibbosities and pharyngeal bulb with two macroplacoids and neither microplacoid nor septulum. It differs from D. macrodon Binda, Pilato & Dastych, 1980, in having no color, indistinct gibbosities, different buccal armature and claws of hind legs shorter than those of the other legs. It differs from D. maranguensis Binda & Pilato, 1995 by: absence of small cuticular tubercles, claws of the hind legs shorter than those of the other legs, small lunules present.